Chemistry - Chang, Raymond
This new edition has been revised throughout to update information and make it more accessible. New three-dimensional illustrations have been incorporated to help students in their learning. The text features "Chemistry in Action" essays and "Applied Chemistry" examples to reinforce students' grasp of concepts and principles. In addition, it features over 250 worked examples to help students to develop their problem-solving skills. Practice exercises accompany each example so that students can immediately check their understanding of the procedures used. This edition features a new chapter covering the many environmental topics of "Chemistry in the Atmosphere". This chapter provides students with a foundation for understanding environmental issues such as indoor pollution, CFCs and the ozone layer